The effect of the choice of turbulence model on the simulation of fluid flow on a centrifugal separator - Colman, Alejandro; Rincón, José; Araujo, Carlos; Materano, Gilberto; Reyes, Miguel (Revista Técnica de la Facultad de Ingeniería. Universidad del Zulia)
Véase archivo PDF